(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Corneal blindness is a major public health problem and one of the leading causes of visual impairment worldwide. Eye donation remains the only effective means of obtaining donor corneas for corneal transplantation and restoration of vision. Awareness and knowledge regarding eye donation among young adults are essential for improving donation rates. This study was conducted to assess and compare the awareness and knowledge regarding eye donation among medical and non-medical students. Methodology: A cross-sectional questionnaire-based study was conducted in the Department of Ophthalmology, Sree Mookambika Institute of Medical Sciences, Kulasekharam, from March 2024 to February 2025. Undergraduate medical and non-medical students were included after obtaining informed consent. Data were collected using a pretested, semi-structured self-administered questionnaire comprising 21 questions related to awareness, knowledge, sources of information, and willingness toward eye donation. Data were analyzed using SPSS version 25.0, and statistical significance was considered at p<0.05. Results: The majority of participants were aware of eye donation. Among them, 73.42% of medical students and 71.57% of non-medical students correctly identified eye donation as donation of eyes after death. Doctors and healthcare workers were the primary source of information for both groups. Awareness regarding eye banks was higher among medical students (83.21%) compared to non-medical students (55.78%). Only 17.22% of participants knew the correct storage duration of donor corneas. Overall, 77.22% of students expressed willingness to donate their eyes in the future, with greater willingness observed among medical students (81.81%) than non-medical students (72.63%). Conclusion: Although awareness regarding eye donation was high among both medical and non-medical students, important knowledge gaps and misconceptions persist. Medical student’s demonstrated better knowledge and awareness compared to non-medical students. Targeted educational programs and awareness campaigns are needed to improve understanding and encourage eye donation practices among young adults.